2003
DOI: 10.1046/j.1462-5822.2003.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion and survival strategies ofAnaplasma phagocytophilum

Abstract: SummaryAnaplasma phagocytophilum is an aetiological agent of human granulocytic ehrlichiosis, an emerging tickborne zoonosis in the United States and Europe. This obligate intracellular bacterium is unique in that it colonizes polymorphonuclear leucocytes (neutrophils). Neutrophils are key players in innate immunity. These short-lived phagocytes ingest invading microorganisms and destroy them by various means, which include fusing the bacteria-containing phagosome with acidic lysosomes as well as directing tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 103 publications
3
83
0
1
Order By: Relevance
“…Previous studies concerning this phenomenon focused on the effect of the infection on the executionary apoptotic cascade, showing that A. phagocytophilum inhibits neutrophil apoptosis by modulating the extrinsic as well as the intrinsic pathway of apoptosis (9). However, it is still poorly understood which signals regulate this process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concerning this phenomenon focused on the effect of the infection on the executionary apoptotic cascade, showing that A. phagocytophilum inhibits neutrophil apoptosis by modulating the extrinsic as well as the intrinsic pathway of apoptosis (9). However, it is still poorly understood which signals regulate this process.…”
Section: Discussionmentioning
confidence: 99%
“…A. phagocytophilum is able to inhibit host cell apoptosis pathways as a mechanism to improve its survival and multiplication inside the host cell (Rikihisa, 2010). In vertebrates, the pathogen has the ability to delay host cell apoptosis by activation of an anti-apoptotic cascade since this is crucial for its intracellular survival and reproduction in the neutrophils whose life cycle is normally short (Carlyon and Fikrig, 2003;Galindo et al, 2008). Different studies have shown that A. phagocytophilum infection upregulates the expression of anti-apoptotic blc-2 genes, blocks cell surface fatty acid synthase (FAS) clustering during spontaneous neutrophil apoptosis and inhibits cleavage of pro-Caspase 8 and Caspase 8 activation as well as secretion Anaplasma translocated substrate-1 (Ats-1) preventing mitochondrial response to apoptotic signals (Niu et al, 2010;Rikihisa, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Human anaplasmosis (formerly called human granulocytic ehrlichiosis) is an emerging vector-borne infection in the United States and Europe (8,10,15). The causative agent is Anaplasma phagocytophilum, an obligate intracellular bacterium that naturally cycles among ticks of the Ixodes ricinus complex and mammalian hosts (8,15,16).…”
mentioning
confidence: 99%
“…The causative agent is Anaplasma phagocytophilum, an obligate intracellular bacterium that naturally cycles among ticks of the Ixodes ricinus complex and mammalian hosts (8,15,16). Humans are occasional inadvertent hosts.…”
mentioning
confidence: 99%
See 1 more Smart Citation